2020
DOI: 10.1109/access.2020.2986809
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Different Resampling Methods in Predicting Students’ Performance Using Machine Learning Techniques

Abstract: In today's world, due to the advancement of technology, predicting the students' performance is among the most beneficial and essential research topics. Data Mining is extremely helpful in the field of education, especially for analyzing students' performance. It is a fact that predicting the students' performance has become a severe challenge because of the imbalanced datasets in this field, and there is not any comparison among different resampling methods. This paper attempts to compare various resampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 47 publications
1
118
0
5
Order By: Relevance
“…We assimilated the daily PM2.5 measurements, WRF/CMAQ simulations, satellite aerosol optical depth (AOD) from Aqua and Terra MODIS Level 2 products (https://ladsweb.modaps.eosdis.nasa.gov/), meteorological parameters from the Modern-Era Retrospective analysis for Research and Applications Version 2 (MERRA-2) (Randles et al, 2017;Buchard et al, 2017), elevation data from the Global Digital Elevation Model (GDEM) (https://earthexplorer.usgs.gov/), gridded population distributions (Xiao et al, 2021b), and land cover classification data (http://data.ess.tsinghua.edu.cn) (Gong et al, 2019a; to train the PM2.5 prediction model and predicted PM2.5 concentrations during 2000-2018. The detailed data collection and processing methods were summarized in Appendix A.…”
Section: Data For Pm25 Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…We assimilated the daily PM2.5 measurements, WRF/CMAQ simulations, satellite aerosol optical depth (AOD) from Aqua and Terra MODIS Level 2 products (https://ladsweb.modaps.eosdis.nasa.gov/), meteorological parameters from the Modern-Era Retrospective analysis for Research and Applications Version 2 (MERRA-2) (Randles et al, 2017;Buchard et al, 2017), elevation data from the Global Digital Elevation Model (GDEM) (https://earthexplorer.usgs.gov/), gridded population distributions (Xiao et al, 2021b), and land cover classification data (http://data.ess.tsinghua.edu.cn) (Gong et al, 2019a; to train the PM2.5 prediction model and predicted PM2.5 concentrations during 2000-2018. The detailed data collection and processing methods were summarized in Appendix A.…”
Section: Data For Pm25 Modelingmentioning
confidence: 99%
“…A total of 3.9% of the daily data were assigned as high-pollution. Previous studies reported that balancing training data with SMOTE improved the classifiers' performance (Ghorbani and Ghousi, 2020;Saputra and Suharjito, 2019). Thus, we applied the SMOTE algorithm that oversampled the high-pollution data (the minority) by artificially generated new synthetic samples along the line between the high-pollution data and their selected nearest neighbors (Chawla et al, 2002;Chawla et al, 2003).…”
Section: The Two-stage Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This method really helps the predictive models to present excellent and trustable performance [39,40]. In 2020, Ghorbani and Ghousi [41] compared various resampling techniques such as Borderline SMOTE, Random Over Sampler, SMOTE, SMOTE-ENN, SVM-SMOTE, and SMOTE-Tomek to handle the imbalanced data problem while using different datasets. The results of their research work reveal that the SVM-SMOTE is more efficient than the other resampling methods, and this method improves the performance of classifiers.…”
Section: ) Imbalanced Data Problemmentioning
confidence: 99%
“…There are a number of variables that influence the decision to forecast and track student success in educational institutions. Educational institutions' decision-makers use these variables to create or build strategies to enhance and track students' academic performance [5].…”
Section: Introductionmentioning
confidence: 99%